Implementation of social capital for multipurpose cooperative autonomy - Andik Fadjar Tjahjono; Mustain Mashud; Falih Suaedi (Faculty of Social and Political Science, Universitas Airlangga, 2022)
Only a few cooperatives succeed in utilizing social capital, one of them is the Setia Budi Wanita (SBW) Multipurpose Cooperative, East Java. This study aims to elaborate on social capital utilization that develops the autonomy of a multipurpose cooperative. The research method used was qualitative with a phenomenology approach in SBW Multipurpose Cooperative and data were collected through interviews, focused group discussions, and document review. This study has nine informants, including one East Java cooperative figure, four cooperative administrators, two existing members, and two new members. Various data were traced, among others: profiles of SBW figures, various women empowerment programs, the joint responsibility group system, and collaborative partnership between SBW Multipurpose Cooperative and the Department of Cooperatives and SMEs of East Java Province. The results show that SBW Multipurpose Cooperative has various social capital, among others: the characters of Mursia Zaafril Ilyas and Sri Untari Bisowarno, the bond of the seventeen doctors’ wives, a community of 360 members, and fourteen administrators of SBW; values and trust in the network of women’s cooperatives. This study concludes that social capital elements enable SBW Multipurpose Cooperative to be an autonomous cooperative. SBW Multipurpose Cooperative can utilize the collaboration of individual, community, and network social capital.